Sequential dual-targeting biomimetic nanovesicles for bone marrow–specific delivery of bortezomib in multiple myeloma - Lu, Chongyan; Xiao, Zhifang; Zhang, Hanqing; Zhang, Peng; Gao, Yang; Ouyang, Ling; He, Xianjun; Han, Na; Zhang, Jinfeng; Guan, Mengshan; Feng, Yueqi; Li, Yonghua (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionInefficient bone marrow targeting remains a major barrier to improving clinical outcomes in multiple myeloma (MM). Although bortezomib (BTZ), a first-line proteasome inhibitor, exhibits potent antitumor activity, its short half-life, dose-limiting off-target toxicity, and pronounced neurotoxicity severely constrain therapeutic utility.MethodsHere, we report the design of a sequentially dual-targeted biomimetic nanoplatform that integrates the high affinity of alendronate for hydroxyapatite in the bone matrix with the homotypic targeting capability of MM cell membranes, thereby enabling a hierarchical “bone-first, tumor-next” delivery paradigm. This two-stage navigation strategy allows the nanoparticles to anchor specifically within the bone microenvironment and subsequently achieve precise MM cell recognition via membrane adhesion molecules, leading to enhanced intralesional BTZ accumulation and retention.ResultsAs a result, proteasome inhibition and apoptosis induction were markedly amplified. Both in vitro and in vivo studies demonstrated that this nanoplatform significantly prolonged survival in MM-bearing mice: all animals in the PBS control group succumbed within 29 days, whereas 100% of BTZ@PLGA/EM-treated mice survived to day 45 (p < 0.001), accompanied by reduced systemic toxicity.DiscussionCollectively, this work addresses a central challenge of drug delivery within the bone marrow niche and provides a promising strategy with strong translational potential for MM therapy.